Indian Economy: Future Prospects & Challenges - Gupta, Dipika (Prabandhan: Indian Journal of Management, 2009)
India’s economy is diverse, consisting of agriculture, manufacturing, and a multitude of services. The economy of India is currently the twelfth largest in the world, with a GDP of around 1 trillion. For the fiscal year 2007-2008, it recorded a GDP growth rate of 9.0%, thus becoming the second fastest emerging economy, after China. Despite much political turmoil, at this sustained growth rate, economists forecast that India would have a more pronounced economic effect on the world stage, in the coming decades. In 2003, Goldman Sachs predicted that India’s GDP will overtake France and Italy by 2020, Germany, UK and Russia by 2025 and Japan by 2035. By 2035, India will be the third largest economy of the world, behind US and China. The paper has three parts. I part canvassed the condition of Indian economy in pre liberalisation period. II part represents an overview of Indian economy in post liberalisation period and III part has devoted to future prospects and challenges in Indian economy. To achieve the above objectives information and data has been collected from the secondary sources such as books, journals, research papers, websites, periodicals and reports of many government and non-government publications.